Six months to Brexit: how scientists are preparing for the split. (27th September 2018) - Masood, Ehsan; Vesper, Inga; Van Noorden, Richard
Seven researchers and campaigners tellNature how Britain's break-up with the EU is affecting research. Seven researchers and campaigners tell Nature how Britain's break-up with the EU is affecting research